2014
DOI: 10.1074/jbc.m114.562066
|View full text |Cite
|
Sign up to set email alerts
|

Control of the Diadenylate Cyclase CdaS in Bacillus subtilis

Abstract: Background:Bacillus subtilis CdaS is a sporulation-specific diadenylate cyclase. Results: Activity of CdaS is regulated by its N-terminal autoinhibitory domain. Conclusion:The synthesis of c-di-AMP is under tight control in B. subtilis. Significance: The activity of CdaS is governed by a hexamer/dimer transition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
49
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 43 publications
(56 reference statements)
2
49
0
5
Order By: Relevance
“…It has been proposed that the different enzymes form temporally and spatially distinct pools of c-di-GMP which can then participate in specific signal transduction processes (2,49,50). Since CdaS is expressed exclusively under conditions of sporulation, and since the c-di-AMP formed by this enzyme is implicated in spore germination (20), we can assume that CdaS produces a specific pool of c-di-AMP that is relevant only under very specific conditions. For CdaA and DisA, the data suggest a functional spe- cialization: while CdaA seems to be involved in the control of cell wall homeostasis, there is increasing support for the idea that DisA contributes to the control of DNA integrity and to DNA repair (5,13,15,51).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proposed that the different enzymes form temporally and spatially distinct pools of c-di-GMP which can then participate in specific signal transduction processes (2,49,50). Since CdaS is expressed exclusively under conditions of sporulation, and since the c-di-AMP formed by this enzyme is implicated in spore germination (20), we can assume that CdaS produces a specific pool of c-di-AMP that is relevant only under very specific conditions. For CdaA and DisA, the data suggest a functional spe- cialization: while CdaA seems to be involved in the control of cell wall homeostasis, there is increasing support for the idea that DisA contributes to the control of DNA integrity and to DNA repair (5,13,15,51).…”
Section: Discussionmentioning
confidence: 99%
“…The third diadenylate cyclase of B. subtilis, CdaS, is expressed exclusively during sporulation and is required for spore germination. The activity of CdaS is controlled by its N-terminal autoinhibitory domain (20).…”
mentioning
confidence: 99%
“…While cdaA is expressed during vegetative growth, the cdaS gene is expressed during sporulation or germination of spores (7). The cdaS inactivation decreases the germination efficiency of spores, indicating a germination-specific function for this enzyme (8). Recently, it has been shown that c-di-AMP is essential for the growth of B. subtilis (6,9,10).…”
mentioning
confidence: 99%
“…Jörg Stülke (University of Göttingen) showed the latest de-velopment on the c-di-AMP signaling network in B. subtilis. In this organism, c-di-AMP is produced by three diadenylate cyclase (DAC) enzymes, CdaA (or DacA), DisA, and CdaS, and is degraded by the DHH/DHHA1 domain-containing phosphodiesterase GdpP (YybT) and a second predicted phosphodiesterase containing a DH domain with homology to the Listeria monocytogenes enzyme PgpH (85,86). Jörg highlighted the finding that c-di-AMP is the first signaling nucleotide that directly controls both expression and activity of a target protein, KtrA in B. subtilis, by binding to the ydaO riboswitch that is linked to the ktrA gene as well as to the KtrA protein itself.…”
Section: Newcomers In Bacterial Second Messenger Signaling: C-di-ampmentioning
confidence: 99%